2015
DOI: 10.3233/wor-152166
|View full text |Cite
|
Sign up to set email alerts
|

The effects of work surface hardness on mechanical stress, muscle activity, and wrist postures

Abstract: Given the significant reduction in contact pressure and corresponding lower ratings in perceived fatigue, the soft-edge work surface subjectively and objectively improved measures of contact stress which may reduce physical exposures associated with the onset and development of musculoskeletal disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…In a study on truck drivers it was concluded that self-reported cervical herniated disc, nuchal pain, arm/forearm weakness, arm/forearm numbness, and finger numbness were significantly more prevalent as the driver's duration of exposure increased [24]. The findings of a study [25] on truck drivers in USA demonstrated that there were substantial differences in health risk prediction between the predominant axis exposure (advocated by the European Union Vibration Directives) and vector sum exposures.…”
Section: Literature Reviewmentioning
confidence: 94%
“…In a study on truck drivers it was concluded that self-reported cervical herniated disc, nuchal pain, arm/forearm weakness, arm/forearm numbness, and finger numbness were significantly more prevalent as the driver's duration of exposure increased [24]. The findings of a study [25] on truck drivers in USA demonstrated that there were substantial differences in health risk prediction between the predominant axis exposure (advocated by the European Union Vibration Directives) and vector sum exposures.…”
Section: Literature Reviewmentioning
confidence: 94%
“…3. Web-browsing task (dependent variable: the number of questions answered): Web-browsing tasks (Kim, Aulck, Trippany, & Johnson, 2015) consisted of standardized web-browsing activities, which required the participants to visit a off-line website on the computer and read the site contents to answer a question by either typing or choosing an answer with the laptop trackpad. The performance was measured by calculating the number of questions answered correctly.…”
Section: Non-driving Task Performancementioning
confidence: 99%